Practising fiercely : fulfilment through stance, supports and stamina : a participatory narrative inquiry of specialist teachers' practice in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Ph.D. in Education at Massey University, Albany, Aotearoa New Zealand - Holley-Boen, Wendy (Massey University, 2017)
Teachers work within a range of personal and contextual factors that serve as enablers and barriers to their professional identity, practice and wellbeing. There is a need to explore their perspectives of the current education context, and their roles within it, to better understand the ways teachers experience and position themselves within and against the tensions posed by an increasingly complex world. This research is timely as it investigates an emerging group of professionals, specialist teachers in Aotearoa New Zealand, who integrate postgraduate study with new professional roles and the other facets of their lives. Using a participatory narrative inquiry, steeped in positive psychology and biculturally responsive practice, the present study identifies connections across identity, practice and wellbeing as knowing oneself and conceptualizing practice as relational; ecological and contextualized; challenging and requiring lifelong learning. Alongside the enablers of trust and agency, the research foregrounds the tensions of working in a system straddling special and inclusive education and other unintended barriers to professional practice. Enablers, tensions and mediating variables are unpacked with a focus on the way agentic professionals navigate their personal and professional lives. Findings from the present study informed the development of a framework for the fulfilment of teachers through fierce practice comprised of stance, supports and stamina. This framework has utility at the individual level, supporting the fulfilment of individual teachers. At the systems level, the framework may be of interest to tertiary teachers and institutions wishing to help teachers to develop and sustain meaningful and satisfying lives.
Keywords: Special education teachers; Inclusive education; Specialist teaching; New Zealand